2016
DOI: 10.1002/14651858.cd007731.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Ganoderma lucidum (Reishi mushroom) for cancer treatment

Abstract: ects of ganopoly (a Ganoderma lucidum polysaccharide extract) on the immune functions in advanced-stage cancer patients. Immunological

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(75 citation statements)
references
References 30 publications
(15 reference statements)
1
68
1
2
Order By: Relevance
“…Among these five RTCs, four studies showed that patients treated with G. lucidum had relatively improved quality of life compared to controls (73). Our study also showed that BSGLWE protected tumor-bearing mice from weight loss and reduced the degree of malignancy compared to 5-FU or control groups.…”
Section: Discussionmentioning
confidence: 99%
“…Among these five RTCs, four studies showed that patients treated with G. lucidum had relatively improved quality of life compared to controls (73). Our study also showed that BSGLWE protected tumor-bearing mice from weight loss and reduced the degree of malignancy compared to 5-FU or control groups.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, a systematic review evaluates the clinical effects of G. lucidum on long-term survival, tumor response, host immune functions, and quality of life in cancer patients, as well as adverse events associated with its use. The study concluded that incorporation of G. lucidum treatment can improve tumor response of lung cancer to conventional therapy and may enhance immunity by stimulating T-lymphocyte proliferation, suggesting that it is a promising adjunct to counter the unwanted common immunosuppressive effect of many chemotherapeutic drugs [41]. As mentioned in WHO's report, new drugs not necessarily eradicate tumors but, when combined with other agents, may turn cases of fatal cancer into manageable chronic illness.…”
Section: Clinical Studies With Humansmentioning
confidence: 99%
“…A systematic review determining the effectiveness of Lingzhi in treating risk factors of cardiovascular diseases concluded that current evidence is inadequate to support the efficacy of Lingzhi, and the quality of the studies was poor 9 . Another systematic review evaluating the clinical efficacy of Lingzhi found that available evidence was insufficient to justify using Lingzhi for cancer treatment 10 . Therefore, more well‐planned clinical studies are needed to determine the efficacy of Lingzhi regarding all proposed health benefits.…”
Section: Lingzhimentioning
confidence: 99%